2003
DOI: 10.2166/wst.2003.0490
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chlorination of estrogenic chemicals on the level of serum vitellogenin of Japanese Medaka (oryzias latipes)

Abstract: Mature male medaka were continually exposed to four chemicals, p-n-nonylphenol (p-n-NP), nonylphenol (p-NP), bisphenol-A (BPA) and 17beta-estradiol (E2) to evaluate their estrogenic activities in the laboratory. In order to understand the effect of the chlorination that is applied widely in water and wastewater treatment, the above chemicals were chlorinated and then exposed to mature male medaka. Furthermore, in the case of vitellogenin, a is a female specific protein induced by the exposure to test waters co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
1
8
0
2
Order By: Relevance
“…Sohoni et al (2001) demonstrated that BPA induced VTG synthesis in male fathead minnows (Pimephales promelas) at concentrations of 640 and 1280 Ag/ l after 43 days and 160 Ag/l after 71 days. In medaka, Tabata et al (2003) observed marked increases in the serum VTG concentrations of mature male fish after 5 weeks of exposure to 1000 Ag BPA/l. In addition, Kang et al (2002a) demonstrated that concentrations of hepatic VTG were increased significantly in males of reproductive phase treated with BPA at 3120 Ag/l.…”
Section: Discussionmentioning
confidence: 87%
“…Sohoni et al (2001) demonstrated that BPA induced VTG synthesis in male fathead minnows (Pimephales promelas) at concentrations of 640 and 1280 Ag/ l after 43 days and 160 Ag/l after 71 days. In medaka, Tabata et al (2003) observed marked increases in the serum VTG concentrations of mature male fish after 5 weeks of exposure to 1000 Ag BPA/l. In addition, Kang et al (2002a) demonstrated that concentrations of hepatic VTG were increased significantly in males of reproductive phase treated with BPA at 3120 Ag/l.…”
Section: Discussionmentioning
confidence: 87%
“…The chlorination of EDCs might result in a reduction of water estrogenicity [44] or its enhancement [45,46], and, since this is a disputed issue, more research is needed in this area.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al (2002b), using a yeast two-hybrid system showed that aqueous chlorinated 4-NP solutions elicit anti-estrogenic activities. Tabata et al (2003) ascertained by means of vitellogenin synthesis in male Medaka fish that chlorination using 1.5 mg/l NaClO did not increase the vitellogenin synthesis. On the other hand Requena et al (unpublished, cit.…”
Section: -Npmentioning
confidence: 92%